Determinación de áreas vulnerables a la presencia actual y futura de antracnosis (Colletotrichum acutatum) en Zonas productoras de chocho del Cantón Latacunga - Acuña Acuña, Geovana Elizabeth (2017)
The research was done in the bean production zones at Latacunga Canton, with the objective to determine the vulnerable areas to anthracnose (Colletotrichum acutatum); the investigation started with the study of ecology theory as taxonomy and anthracnose symptoms, by the plantation of fungus inside moist chambers at the laboratory, and its observation through the microscope, ratifying the content in the bibliography. It has been made potential distribution models of the specie, with registries of geographic coordinates at the field, five climatic variables were chosen from the WorldClim data that influence in the habitat of the fungus specie, as annual mean temperature, mean diurnal range, isothermally, precipitation of the driest month and the precipitation seasonality in MaxEnt program. With the CMIP3 method the comparison between actual potential distribution and future one was made, where the area under the curve is higher to 0,75 demonstrating precision; also, with a CCCMA global circulation model where 11 de Noviembre Parish has more incidence and probabilities to future of maintaining the presence of anthracnose. Toacaso Parish has lower probability rate of anthracnose existence, this is represented in distribution maps. The identification of vulnerable areas is useful to give recommendations that allow minimize the impact of the pathogen on crops in the futu